(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Kefir is a fermented dairy product that contributes to health due to its probiotic and functional effects. Moringa is a plant that has medicinal and nutritional properties, mainly due to its content of vitamins A and C, calcium, iron, and potassium. The purpose of this study was to develop mango kefir supplemented with moringa as an alternative protein source. Three formulations were developed: Control (kefir), mango kefir, and mango kefir with moringa. The product was characterized through physicochemical, proximate, microbiological, and sensory analysis. The proximate analysis revealed that the mango kefir with moringa formulation had the highest percentages of protein (4.1%), ash (0.7%), and fiber (1%) compared to the other formulations. The product met the microbiological parameters established in the current health regulations. The sensory analysis showed that mango kefir had the highest scores in all attributes; however, mango kefir with moringa also had good acceptance. Mango kefir supplemented with moringa represents an alternative protein consumption option.